DENGUE RISK FACTOR IN BANGUNTAPAN III PHC, BANTUL, INDONESIA - Devi Stevani; Himatul Husna; Muthia Ardiyanti; Yuni Andira Sari; Desi Nurfita; Sugiarto Sugiarto; Siti Nurkhoiriyah (Universitas Ahmad Dahlan, 2020)
Background: Dengue Haemorrhagic Fever (DHF) is an infectious disease caused by Aedes aegypti mosquito. DHF is widespread in some regions, with the number of patients continues to increase every year. This study aimed to determine the risk factors for DHF include 3M + program implementation, residential distance, hanging clothes habit, napping habit, repellent usage, and sunlight conditions.Method: Analytic study with case-control approach was used in this study. Samples consist of case and control. Of 16 cases and 32 controls were participated in this study who purposively selected. Data were collected using a questionnaire. Univariate and bivariate using chi-square tests were employed to analyze the result.Result: Three variables are associated with the incidence of dengue: napping habit (OR=11.667), residential distance (OR=1.696), and sunlight condition (OR=0.0289).Conclusions: napping habit, residential distance, and Sunlight Conditions are a risk factor of DHF.